Urban Canyon Configurations for Sustainable Tropical Cities: A Simulation for Design Practice - Iyati, Wasiska; Citraningrum, Andika; Wardoyo, Jono (Institut Teknologi dan Bisnis Ahmad Dahlan, 2026)
Urban overheating and limited daylight access are persistent challenges in rapidly densifying tropical cities. This study examines the influence of urban canyon geometry—including building width-to-length ratio, corridor width, and lateral spacing—on surface temperature dynamics and daylight performance. Using Autodesk Forma, 27 building massing configurations were simulated under standardized conditions with a fixed building height of 30 meters and a footprint of 900 m². Surface temperatures were measured at corridor and rear façade points at 10:00 a.m. and 2:00 p.m., while daylight performance was assessed using sun hours and daylight potential indicators. The results indicate that compact building forms with minimal spacing exacerbate heat accumulation and restrict daylight access, whereas configurations with greater spatial permeability enhance both thermal and lighting performance. The optimal configuration featured an elongated building ratio of 1:3, a narrow corridor width of 15 meters, and wide lateral spacing of 30 meters, achieving corridor surface temperatures as low as 33°C and daylight performance values of up to 66%. Beyond its analytical findings, this study highlights the practical applicability of Autodesk Forma as an accessible and user-friendly tool for early-stage massing studies. Compared to more complex simulation platforms such as ENVI-met or CFD, Autodesk Forma enables architects and designers to conduct simple yet effective climate-responsive analyses during the initial phases of building and site design, thereby supporting sustainable urban development in tropical contexts.